Delayed presentation of congenital diaphragmatic hernia with strangulated bowel - Felippe Flausino, M.Sc; Luiza Maes Manara; Johny Grechi Camacho; Jose Antônio de Souza, Phd (Elsevier, 2022)
Congenital diaphragmatic hernia (CDH) is a frequent malformation (1 per 5000 births)(1). The diagnosis occurs frequently during prenatal assessment, however, in Brazil, it occurs in less than half of the cases (41%)(2) which may represent a bigger rate of delayed diagnosis. The relevance and challenge of this case lie in the technical difficulty in reaching the correct diagnosis in a pediatric emergency, with a late clinical presentation and doubtful imaging exams. The delay in diagnosis can lead to serious consequences. Objective: To report a case of late-presenting and complicated CDH with intestinal strangulation, explaining the surgical treatment performed and reviewing literature. Results: Infant, male, 7 months old, presenting with vomiting, dehydration, dyspnea, and decreased breath sounds on the left hemithorax. A chest radiograph with left hemithorax opacification led to chest drainage. A chest CT suggested diaphragmatic hernia. Emergency surgery was performed due to hypovolemic shock, evidencing strangled intestinal loops herniating through a left posterolateral diaphragmatic defect. After the herniated viscera were reduced, in an attempt to avoid a near total enterectomy, it was decided to wait 12 hours and then perform a second look procedure, in which it was possible to save 1 m of small bowel. After performing the enterectomy and jejunostomy the child presented food tolerance and good evolution. The jejunostomy was closed before hospital discharge. He was clinically well after 6 months of postoperative follow-up. Discussion: Late presenting CDH occurs mostly on the left (90%, bilaterality is extremely rare - less than 1%). The diagnostic of a delayed CDH is a challenge, mainly because of its varied presentations. The surgical indication depends on the patient clinical condition and, in this report, it was an emergency due to hypovolemic shock related to bowel strangulation. Final considerations: Late CDH should be considered in children with respiratory and/or digestive symptoms in association with suggestive imaging exams. Emergency surgery should be promptly performed if the clinical condition is associated with unresponsive hypovolemic shock.